ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN KINERJA PADA KARYAWAN PT BPR SEHAT SEJAHTERA DI TANGERANG SELATAN - Nuryadi, Nuryadi; Ida Nurlina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study focuses on analyzing work motivation in improving employee performance at PT BPR Sehat Sejahtera. The purpose of this research is to examine the extent to which work motivation influences employee performance and to identify the factors that drive or hinder motivation. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with four purposively selected informants from different divisions. The results show that employee motivation is influenced by five main indicators: physiological needs (bonuses and allowances), safety needs (health benefits and a secure work environment), social needs (peer relationships), esteem needs (recognition for achievements), and self-actualization needs (opportunities for development and promotion). Overall, high work motivation has a positive impact on employee performance, including quality, quantity, timeliness, cost efficiency, and interpersonal relationships. The study recommends that the company strengthen its reward system, provide more opportunities for career development, and maintain a supportive work environment to sustain employee motivation and productivity..